Sociodemographic and early-life predictors of being overweight or obese in a middle-aged UK population– A retrospective cohort study of the 1958 National Child Development Survey participants - Glenna Nightingale; Karthik Mohan; John Frank; Sarah Wild; Sohan Seth (PLoS ONE, 2025)
Obesity has become a global public health concern. However, its precise origins and causation are still hotly debated, especially the relative importance of individual-level genetics and behaviours, as opposed to obesogenic environmental factors. Our key objective is to quantify the impact of sociodemographic and early-life course predictors of being overweight or obese at 16, being overweight/obese/severely obese42 years of age, and on the incidence of a status of being overweight/obese/severely obese between 16 and 42 years of age, spanning the years before and after marked increases in obesity prevalence in the UK. We used data collected from participants and their mothers from the 1958 National Child Development Survey. The outcomes of interest were being overweight (defined as 25kg/m2<BMI≤29.9kg/m2 ) or obese (defined as BMI > 30 kg/m2) at 16 and 42 years of age and incident obesity between 16 and 42 years of age. We assessed the risk factors for obesity using logistic regression models. We observed a strong influence of maternal obesity for being Obese/Severe Obese compared to being overweight across the three models (ORs 4.328,2.901,3.293 for the models relating to age 16, the age range 16-42, and age 42 respectively). Additionally, we note that maternal smoking (ORs 1.6 to 1.8 for 10 + cigarettes per day compared to non-smokers) on all three outcomes were statistically significant. Females were prone to being overweight/obese at 16 years of age (OR 1.96 CI 1.61 to 2.39) but less prone to develop obesity between 16 and 42 years of age (OR 0.89 CI 0.78 to 1.007). Our results suggest that sociodemographic and early-life risk factors could be used to target obesity prevention programmes for children and adults. In particular, we note that the effect of maternal influences persists through to age 42 and that strikingly, those predictors were just as powerful (and prevalent) in the era before the current obesity pandemic began. This suggests that, as Geoffrey Rose pointed out, novel studies are needed of factors at the community/societal level that may have caused the current obesity pandemic, since individual-level risk factors appear not to have changed over the time period spanning the pandemic’s onset and growth.